Liposomes modified with double-branched biotin: A novel and effective way to promote breast cancer targeting. Issue 14 (15th July 2019) - Lu, Runxin; Zhou, Lin; Yue, Qiming; Liu, Qijun; Cai, Xiaojing; Xiao, Wenjiao; Hai, Li; Guo, Li; Wu, Yong
Graphical abstract: Abstract: Although active targeting liposomes with cancer-specific ligands can bind and internalize into cancer cells, only a few high-efficiency liposomes have been developed so far because traditional single branched ligand modified liposomes generally failed to deliver adequate therapeutic payload. In this paper, we broke the traditional design concept and synthesized the double branched biotin modified cholesterol (Bio2 -Chol) for the first time. On this basis, different biotin density modified liposomes ((Bio-Chol)Lip, (Bio-Chol)2 Lip and (Bio2 -Chol)Lip) were successfully prepared and used as active targeting drug delivery systems for the treatment of breast cancer. The in vitro and in vivo breast cancer-targeting ability of these liposomes were systemically studied using paclitaxel (PTX) as the model drug. And the uptake mechanism of (Bio2 -Chol)Lip was investigated. The results showed that (Bio2 -Chol)Lip had the best breast cancer-targeting ability compared with naked paclitaxel, unmodified Lip, (Bio-Chol)Lip and (Bio-Chol)2 Lip. In particular, the relative uptake efficiency (RE) and concentration efficiency (CE) of (Bio2 -Chol)Lip were respectively enhanced by 5.61- and 5.06-fold compared to that of naked paclitaxel. Both distribution data and pharmacokinetic parameters suggested that the double branched biotin modified liposome ((Bio2 -Chol)Lip) is a very promising drug delivery carrier for breast cancer.